Humanized mice in dengue research: a comparison with other mouse models (2020)
Abstract: Dengue virus (DENV) is an arbovirus of the Flaviviridae family and is an enveloped virion containing a positive sense single-stranded RNA genome. DENV causes dengue fever (DF) which is characterized by an undifferentiated syndrome accompanied by fever, fatigue, dizziness, muscle aches, and in severe cases, patients can deteriorate and develop life-threatening vascular leakage, bleeding, and multi-organ failure. DF is the most prevalent mosquito-borne disease affecting more than 390 million people per year with a mortality rate close to 1% in the general population but especially high among children. There is no specific treatment and there is only one licensed vaccine with restricted application. Clinical and experimental evidence advocate the role of the humoral and T-cell responses in protection against DF, as well as a role in the disease pathogenesis. A lot of pro-inflammatory factors induced during the infectious process are involved in increased severity in dengue disease. The advances in DF research have been hampered by the lack of an animal model that recreates all the characteristics of this disease. Experiments in nonhuman primates (NHP) had failed to reproduce all clinical signs of DF disease and during the past decade, humanized mouse models have demonstrated several benefits in the study of viral diseases affecting humans. In DENV studies, some of these models recapitulate specific signs of disease that are useful to test drugs or vaccine candidates. However, there is still a need for a more complete model mimicking the full spectrum of DENV. This review focuses on describing the advances in this area of research.